1985
DOI: 10.1289/ehp.856393
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum in acidic surface waters: chemistry, transport, and effects.

Abstract: Ecologically significant concentrations of Al have been reported in surface waters draining "acid-sensitive" watersheds that are receiving elevated inputs of acidic deposition. It has been hypothesized that mineral acids from atmospheric deposition have remobilized Al previously precipitated within the soil during soil development. This Al is then thought to be transported to adjacent surface waters.Dissolved mononuclear Al occurs as aquo Al, as well as OH-, F-, SO42-, and organic complexes. Although past inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
38
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(42 citation statements)
references
References 42 publications
4
38
0
Order By: Relevance
“…Though pH tolerance levels offer a general ranking of each species' sensitivity in acidified systems, many studies have shown that other factors such as Al im , DOC, and Ca 2+ , along with the timing and magnitude of episodic fluctuations in toxic acid and Al im concentrations, are strongly related to the degree of stream acidification and influence fish survival in natural systems (Baker et al, 1990;Gagen et al, 1993;Simonin et al, 1993;Van Sickle et al, 1996;Baldigo and Murdoch, 1997). Aluminum fractionation and Al im concentration are also directly dependent upon pH levels (Driscoll, 1985) and both acidity and Al im act in a similar manner to affect fish survival (Wood et al, 1990). These findings imply that the degree of stream acidification and related differences in stream-water chemistry may be primarily responsible for the restricted distributions of most fish-species' populations in the Neversink river, and in other similarly acidified riverine systems.…”
Section: Discussionmentioning
confidence: 99%
“…Though pH tolerance levels offer a general ranking of each species' sensitivity in acidified systems, many studies have shown that other factors such as Al im , DOC, and Ca 2+ , along with the timing and magnitude of episodic fluctuations in toxic acid and Al im concentrations, are strongly related to the degree of stream acidification and influence fish survival in natural systems (Baker et al, 1990;Gagen et al, 1993;Simonin et al, 1993;Van Sickle et al, 1996;Baldigo and Murdoch, 1997). Aluminum fractionation and Al im concentration are also directly dependent upon pH levels (Driscoll, 1985) and both acidity and Al im act in a similar manner to affect fish survival (Wood et al, 1990). These findings imply that the degree of stream acidification and related differences in stream-water chemistry may be primarily responsible for the restricted distributions of most fish-species' populations in the Neversink river, and in other similarly acidified riverine systems.…”
Section: Discussionmentioning
confidence: 99%
“…Stream acidification and mobilization of potentially toxic Al species are especially important concerns because many streams in the northeastern USA are already acidic and contain elevated Al concentrations due to acidic deposition (Driscoll, 1985;Johnson et al, 1981). The increased acidification caused by forest harvesting may therefore contribute additional stress to the aquatic ecosystem.…”
Section: Introductionmentioning
confidence: 99%
“…The speciation of Al was not determined in the treatments. Fluoride was negligible in the treatments, as is common for most soft- water lakes in the mid-west (Cook et al, 1986), so Al-fluoride complexes were unimportant in this experiment, although they can be the dominant form in Adirondack lakes (Driscoll, 1985). We expected that the Al bound to the ligands in the natural lake water of the treatments would mimic Al activity in lakes of similar chemistry.…”
Section: Discussionmentioning
confidence: 91%
“…However, the plankton in the treatments may have experienced the additions of Al as a toxic pulse of inorganic monomeric Al, which became less toxic as it was bound to ligands in the solution. Plankton may also experience pulses of toxic Al in the form of hydrologic events that introduce large amounts of labile monomeric Al to surface waters (Driscoll, 1985). For instance, poorly-buffered northern lakes commonly undergo a pulse of Al-rich, acidic water from spring snowmelt into their surface waters (B. WonsonLiukkonen, pers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation